Drying of sausages made from the meat of black and white pigs: Numerical modeling and structural investigation. Issue 6 (26th April 2017) - Baldino, Noemi; Gabriele, Domenico; Gentile, Luigi; Carnevale, Ilaria; Lupi, Francesca R.; de Cindio, Bruno; De Luca, Maria C.
ABSTRACT: In the present work, dry curing of a specific type of sausage, produced in south Italy, was investigated. The drying process was modeled solving heat and mass transfer balance equations in a 3-D domain corresponding to the real shape of the products, and a good agreement with experimental results was obtained. NMR was used to evidence the differences among the meats of white and black pigs, adopted as raw materials. Owing to these differences, high-quality products can be obtained by tuning the operating conditions as a function of the processed meats and the proposed model can be useful in this.